TRADE LIBERALIZATION AND ECONOMIC GROWTH IN NIGERIA: A COINTEGRATION ANALYSIS (1980-2015) - Ejike, Daniel; ARINZE, ANAH STANLEY; CHIDI, ONWUCHEKWA FAITH (IJRDO - Journal of Business Management, 2018)
This study examined the effect of trade liberalization on economic growth in Nigeria, using the Gross domestic product (GDP) as proxy for economic growth. The study made use of set of data that spanned (1980 – 2015). Ordinary Least Squares (OLS) was used in estimating the effect of trade liberalization on economic growth in Nigeria with a view to ascertaining whether long-run relationship exists between the two and also used in verifying for structural change that may have occurred within the implementation period of a free trade regime that started in 1986. Data for the study were sourced from World Development Indicators (WDI) of the World Bank and Statistical Bulletin of the Central Bank of Nigeria (CBN) various issues. Results indicate that liberalization has positive and significant effect on economic growth in Nigeria, with an evidence of a long-run relationship. Similarly, strong evidence was found to support structural change that took place in 1986 when free trade policy was adopted. The results also presented a violation of the a priori in the case of export and import which showed negative and positive signs respectively. In the light of the above, it was recommended among others that an enabling environment should be provided by the government in the areas of infrastructural facilities to boost domestic production, revitalize ailing industries to enable them produce goods that can compete favourably with their foreign counterparts in the international market to enhance further growth in Nigerian economy.